Primary Phagocytosis of Neurons by Inflamed Microglia: Potential Roles in Neurodegeneration - Neher, Jonas J.; Neniskyte, Urte; Brown, Guy C. (Frontiers in Pharmacology, 2012)
Microglial phagocytosis of dead or dying neurons can be beneficial by preventing the release of damaging and/or pro-inflammatory intracellular components. However, there is now evidence that under certain conditions, such as inflammation, microglia can also phagocytose viable neurons, thus executing their death. Such phagocytic cell death may result from exposure of phosphatidylserine (PS) or other eat-me signals on otherwise viable neurons as a result of physiological activation or sub-toxic insult, and neuronal phagocytosis by activated microglia. In this review, we discuss the mechanisms of phagocytic cell death and its potential roles in Alzheimer’s Disease, Parkinson’s Disease, and Frontotemporal Dementia.